Gendered Power Struggles: A Critical Discourse Analysis of Restrictive Practice in Contemporary Journalism Under Taliban Regime - Rahman, Fadhlur; Zanzibar, Zanzibar; Yuzar, Ella; Sari, Dwhy Dinda (Tribakti: Jurnal Pemikiran Keislaman, 2024)
This study investigates the complex relationship between power dynamics, gender inequalities, and ideological influence in the field of journalism during the Taliban regime's rule. Critical Discourse Analysis (CDA) is used in this study to investigate the various constraints faced by female journalists and media workers. This research paper investigates the consequences of limited information access, as well as widespread arrests and intimidation by both government officials and fighters. The study also looks into the Taliban's strict limitations on media activities, such as the division of workspaces, the requirement for women to cover their faces while on screen, and the regulation of analyst involvement in political programming. The intricate power dynamics that underpin their narratives are revealed through this analysis. The de facto government and combatants are portrayed as entities attempting to maintain their authority, whereas the Taliban attempts to impose regressive ideologies to women who work in news media.